2017
DOI: 10.1177/2041669517718697
|View full text |Cite
|
Sign up to set email alerts
|

A Matched Comparison Across Three Different Sensory Pairs of Cross-Modal Temporal Recalibration From Sustained and Transient Adaptation

Abstract: Sustained exposure to an asynchronous multisensory signal causes perceived simultaneity to shift in the direction of the leading component of the adapting stimulus. This is known as temporal recalibration, and recent evidence suggests that it can occur very rapidly, even after a single asynchronous audiovisual (AV) stimulus. However, this form of rapid recalibration appears to be unique to AV stimuli, in contrast to recalibration following sustained asynchronies which occurs with audiotactile (AT) and visuotac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 39 publications
(89 reference statements)
1
19
1
Order By: Relevance
“…Previous studies reported rapid recalibration effects for audio–visual stimuli, but were unable to demonstrate rapid recalibration for visuo–tactile stimuli (van der Burg et al 2015b ; Alais et al 2017 ). A major difference between our study and previous studies is the length of the SOAs between visual and tactile stimuli.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Previous studies reported rapid recalibration effects for audio–visual stimuli, but were unable to demonstrate rapid recalibration for visuo–tactile stimuli (van der Burg et al 2015b ; Alais et al 2017 ). A major difference between our study and previous studies is the length of the SOAs between visual and tactile stimuli.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, studies have shown that temporal recalibration can be induced even by a single trial, the so-called rapid recalibration (van der Burg et al 2013 , 2015b ). Unlike recalibration following sustained adaptation, rapid recalibration has been reported only for audio–visual stimuli, while it was absent for visuo–tactile stimuli (van der Burg et al 2015b ; Alais et al 2017 ). In the present study, however, we were able to demonstrate rapid recalibration for visuo–tactile stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In broader terms, serial dependence in variance judgments could be regarded as part of a generic strategy of mirroring or transferring trusted decisions. This explanation could also encompass the negative serial dependence associated with low confidence (as a repulsion away from judgments deemed unreliable); however, the different timescales over which the positive and negative biases operate suggest that they are independent mechanisms rather than two aspects of a confidence-based strategy (Alais, Ho, & Han, 2017).…”
Section: Discussionmentioning
confidence: 99%